2021
DOI: 10.3390/jcm10132771
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers in Heart Failure: New Insight in Pathophysiology and Clinical Perspective

Abstract: Heart failure (HF) is a complex clinical syndrome with a huge social burden in terms of cost, morbidity, and mortality. Brain natriuretic peptide (BNP) appears to be the gold standard in supporting the daily clinical management of patients with HF. Novel biomarkers may supplement BNP to improve the understanding of this complex disease process and, possibly, to personalize care for the different phenotypes, in order to ameliorate prognosis. In this review, we will examine some of the most promising novel bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 98 publications
1
32
0
Order By: Relevance
“…The important prognostic role of sST2 has already been established in several previous studies [10,12,27,29,45] and our results just further ascertained that sST2 is an important predictor of mortality, both in-hospital and at 1-month follow-up. Beside the fact that sST2 was significantly associated with short-term adverse outcomes in patients with acute HF enrolled in our study, we can also consider it as a useful tool for patients' follow-up, whether they are presenting stable or decompensated HF.…”
Section: Discussionsupporting
confidence: 87%
“…The important prognostic role of sST2 has already been established in several previous studies [10,12,27,29,45] and our results just further ascertained that sST2 is an important predictor of mortality, both in-hospital and at 1-month follow-up. Beside the fact that sST2 was significantly associated with short-term adverse outcomes in patients with acute HF enrolled in our study, we can also consider it as a useful tool for patients' follow-up, whether they are presenting stable or decompensated HF.…”
Section: Discussionsupporting
confidence: 87%
“…Increasing evidence exists to support the role of the heightened inflammatory milieu present in DM with progression of diastolic dysfunction. DM is associated with increased concentration of serum inflammatory markers such as C-reactive protein (CRP), soluble suppression of tumorgenesis-2 (sST2), galectin-3, C-terminal propeptide of procollagen type I (PICP), N-terminal propeptide of procollagen type III (PIIINP), matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of matrix proteinase-1 (TIMP-1) [ 24 ]. It has been shown that patients with HFpEF and DM have higher levels of (PIIINP), galectin-3 (Gal-3), and TIMP-124.…”
Section: Reviewmentioning
confidence: 99%
“…The same authors also found that the evaluated athletes had similar sST2 concentrations as patients with chronic or even acute heart failure at the start line and after the marathon, respectively [ 86 , 88 ]. sST2 is a proven predictor for mortality and poor outcome in HF [ 89 , 90 , 91 ], and therefore it is controversial that apparently healthy athletes express such high values of sST2. A reasonable explanatory hypothesis is that elevated sST2 concentrations in athletes may be induced by regular exposure to increased cardiac strain during exercise, as this may trigger the cardiac myocytes to release sST2 in circulation.…”
Section: The Soluble Tumor Necrosis Factor-like Weak Inducer Of Apoptosis Soluble Cluster Differentiation 163 and Sst2: Promising Perspecmentioning
confidence: 99%